2020
DOI: 10.1097/ta.0000000000003044
|View full text |Cite
|
Sign up to set email alerts
|

The DISTANCE study: Determining the impact of social distancing on trauma epidemiology during the COVID-19 epidemic—An interrupted time-series analysis

Abstract: BACKGROUND:The large-scale social distancing efforts to reduce SARS-CoV-2 transmission have dramatically changed human behaviors associated with traumatic injuries. Trauma centers have reported decreases in trauma volume, paralleled by changes in injury mechanisms. We aimed to quantify changes in trauma epidemiology at an urban Level I trauma center in a county that instituted one of the earliest shelter-in-place orders to inform trauma care during future pandemic responses. METHODS:A single-center interrupted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 22 publications
8
53
4
Order By: Relevance
“…Although some reports have described decreases in pediatric trauma volumes during the COVID-19 pandemic,[ [6] , [7] , [8] , [9] , 15 ] we found overall rates of pediatric trauma activations in LA County did not change significantly compared to the pre-pandemic period. After the California statewide stay-at-home order on March 19 th , 2020, in LA County there were 3 additional dates in 2020 when pandemic control measures were substantially changed.…”
Section: Discussioncontrasting
confidence: 80%
“…Although some reports have described decreases in pediatric trauma volumes during the COVID-19 pandemic,[ [6] , [7] , [8] , [9] , 15 ] we found overall rates of pediatric trauma activations in LA County did not change significantly compared to the pre-pandemic period. After the California statewide stay-at-home order on March 19 th , 2020, in LA County there were 3 additional dates in 2020 when pandemic control measures were substantially changed.…”
Section: Discussioncontrasting
confidence: 80%
“…Many other studies regarding trauma have found similar increases in penetrating trauma. Southern California 24 penetrating trauma increased from 10.3% to 13.0%, A Los Angeles County study 20 separately identified increase in penetrating trauma 15.4% to 15.7%, Philadelphia 19 penetrating trauma increased 17.5% to 23.7%, and San Francisco 16 violence related injuries increased 17% to 46%. This study identified a concurrent decrease in blunt trauma accompanying the increased proportions of penetrating trauma which is similar to previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, Philadelphia, a major urban city with high pre-COVID rates of violence and which was reported on by three studies, reflected a consistent increase in the proportion of violent trauma regardless of duration at two weeks 19 or 119 days 22 (of note: the third study, with duration of 41 days, found no change in violent trauma when assessment was limited to non-accidental pediatric trauma). 37 It was beyond the scope of this work to establish and assess, per city included in this study, a rating of "high" versus "low" pre-COVID violent trauma burden.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 66%
“…Of these two, one study was limited to examination of cases of pediatric non-accidental trauma. 37 Of the four remaining US-based studies, ranging from 71 -181 days, three found no change in violent trauma 22,32,39 and one found increased incidence. 27 Among the nine studies that statistically examined changes in violent trauma (duration 13 -90 days), only the longest study, Salzano and colleagues, noted a decrease in violent trauma.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 98%
See 1 more Smart Citation